2018
DOI: 10.18632/oncotarget.25966
|View full text |Cite
|
Sign up to set email alerts
|

Online structure-based screening of purchasable approved drugs and natural compounds: retrospective examples of drug repositioning on cancer targets

Abstract: Drug discovery is a long and difficult process that benefits from the integration of virtual screening methods in experimental screening campaigns such as to generate testable hypotheses, accelerate and/or reduce the cost of drug development. Current drug attrition rate is still a major issue in all therapeutic areas and especially in the field of cancer. Drug repositioning as well as the screening of natural compounds constitute promising approaches to accelerate and improve the success rate of drug discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
0
39
0
Order By: Relevance
“…As the aim of this work was to identify previous clinically investigated and approved drugs for repurposing to treat COVID-19 infections, we made use of an MTiOpenScreen database Drugslib that contains 7,173 stereoisomers corresponding to 4574 "approved" drugs [22,23]. Among them, the nsp16 natural ligand SAM, which is used for therapies against depression, liver disorders, fibromyalgia, and osteoarthritis, would serve as a positive control for virtual screening [24].…”
Section: Virtual Screening Of Drugs Against Nsp16 Of Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…As the aim of this work was to identify previous clinically investigated and approved drugs for repurposing to treat COVID-19 infections, we made use of an MTiOpenScreen database Drugslib that contains 7,173 stereoisomers corresponding to 4574 "approved" drugs [22,23]. Among them, the nsp16 natural ligand SAM, which is used for therapies against depression, liver disorders, fibromyalgia, and osteoarthritis, would serve as a positive control for virtual screening [24].…”
Section: Virtual Screening Of Drugs Against Nsp16 Of Sars-cov-2mentioning
confidence: 99%
“…Among the five currently available nsp16 structures of SARS-CoV-2 (April 30, 2020), we selected the 6W4H PDB structure which presents the best resolution (1.8 Å) to screen the Drugslib using the MTiOpenScreen service [22]. The computations of MTiOpenScreen were carried out with AutoDock Vina, a gradient optimization algorithm, which provided a list of the 1,500 highest-scoring compounds [22,23,25]. We repeated the MTiOpenScreen screening protocol three times using the 6W4H structure to ensure the reliability of the results.…”
Section: Virtual Screening Of Drugs Against Nsp16 Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…17449 additional molecules were extracted from Wikipedia Chemical Structures using utilities implemented in the DataWarrior package 28 . Molecules were agged using our FAF-Drug server 29 to remove compounds with inorganic atoms and molecules with unwanted toxicophores as reported in a previous study but keeping molecules even if they could not be found in commercial vendor catalogs 30 . Salts and duplicates were also removed.…”
Section: Structure-based Virtual Screeningmentioning
confidence: 99%
“…The discovery of new uses is an important direction for new drug discovery, and this is drug repositioning [53] . The new drugs discovery through new uses of existing drugs has significantly reduced the cost of research and development, expanded the indications and clinical treatment scope of the original drugs, and the clinical application has tended to be safe, reasonable and effective, with reducing the risk of discovering new drugs in the traditional way at the same time [54] . Drug repositioning strategy is one of the best risk-benefit ratio strategies in the currently known drug discovery strategies, and it is also one of the effective methods to solve the dilemma of high investment and low success rate in new drug discovery [55][56][57] .…”
Section: Technological Development Focusmentioning
confidence: 99%